Students’ struggles with EMI in Kazakhstani universities - M. A. Tajik; G. Y. Akhmetova; L. N. Fillipova; D. A. Shamatov; G. D. Zhunussova (Образование и наука)
Introduction. Fascination with English medium instruction (EMI) is fast growing in higher education institutions in non-native English-speaking countries, including Kazakhstan. The Kazakhstani government adopted a trilingual education policy in 2007 and the Bologna Process in 2010. Both these initiatives motivated universities to offer academic programmes in the English language. As a result, EMI programmes are offered in over 70 higher education institutions across Kazakhstan. In addition, there are four major Kazakhstani universities which offer academic programmes in English only. Despite the increase in the number of EMI programmes, there is a lack of empirical evidence about the difficulties and challenges faced by students in the EMI programmes.Aim. The present study aimed to investigate the nature, forms, and levels of challenges graduate students face in academic reading and writing in English and the way they cope with these challenges. The study was conducted with graduate students and faculty in 10 selected Kazakhstani universities, which offer academic programmes in EMI.Research methodology and methods. The study is based on a mixed-method design, involving an online survey and semi-structured interviews. The closed-ended questions have been analysed using SPSS software (Statistical Package for the Social Sciences). The grounded theory analysis was utilised to scrutinise open-ended questions and interview transcripts.Results and scientific novelty. The study’s results indicated two major challenges faced by graduate students in academic reading and writing: the personal-psychological challenge and sociological challenge. The first challenge includes students’ previous academic backgrounds, exposure, and learning experiences. The second challenge is related to English academic culture and students’ worldviews, concepts, and values about English as a language and medium of instruction. As a result, graduate students experienced a lack of vocabulary, inadequate academic literacy skills, unfamiliarity with academic writing styles in English, and lack of skills to synthesise reading materials.Practical significance. Hence, this study recommends systematising English language programmes across secondary and higher education institutions to help students acquire advanced English language proficiency. Also, the study results suggest that local faculty members should be trained according to international standards in terms of their English language skills and innovative teaching methods.